Prospects for the sulfur-containing amino acids medicines usage for trimethylamine-N-oxide biosynthesis modulation in humans - I. O. Melnychuk; M. L. Sharaieva; V. N. Kramarova; V. H. Lyzohub (Zaporozhye State Medical University, 2023)
The aim: to identify prospects for the sulfur-containing amino acids medicines usage for trimethylamine oxide (TMAO) biosynthesis modulation in humans. Intestinal microbiome and its metabolic products are currently widely discussed as a new therapeutic target for the treatment of cardiovascular, neurological and metabolic diseases. The effect of the intestinal microbiome on human health is unconditional. Its metabolites, including trimethylamine (TMA), TMAO and plasma amino acids, play an important role in the mechanisms of many diseases. The synthesis of TMAO directly depends on such factors as diet, intestinal microbiome status, genetic characteristics of the human body (activity and type of hepatic flavin monooxygenase). At the same time, all these factors are also able to affect the metabolism of sulfur-containing amino acids in the human body. Conversely, sulfur-containing amino acids are able to simulate the state of the intestinal microbiome and the activity of hepatic flavin monooxygenase. Today many sulfur-containing amino acid drugs are widely used in therapeutic practice (taurine, methionine, glutathione), including for the cardiovascular and metabolic diseases treatment. Their effect on the state of the intestinal microbiome and its metabolites is still unexplored. There are currently no strong clinical studies for the use of amino acid preparations to reduce plasma TMAO levels, although this perspective is interesting. The possibility of using taurine is questionable as it affects the state of the intestinal microbiome in ultra-high doses (more than 3 g/day), which can cause side effects. Glutathione drugs have low bioavailability due to its physical and chemical properties, and therefore have not become widespread in therapeutic practice. Drugs that activate glutathione synthesis - for example, selenium derivatives, glutoredoxins, some heat shock proteins (HPS70) actions are not studied in vivo enough. Unfortunately, methionine preparations, on the other hand, increase plasma TMAO levels. Conclusions. Despite the deep pathogenetic affinity of sulfur-containing amino acids and TMAO synthesis, the prospect of using these amino acids drugs to reduce TMAO synthesis is questionable. The problem of reducing the synthesis of TMAO in the human body remains unsolved and requires further search for promising pathogenetically drugs for its correction.